Facile Synthesis of Pt–Pd Alloy Nanocages and Pt Nanorings by Templating with Pd Nanoplates. Issue 12 (29th September 2016) - Wang, Xue; Luo, Ming; Huang, Hongwen; Chi, Miaofang; Howe, Jane; Xie, Zhaoxiong; Xia, Younan
Abstract: We report a facile method for the synthesis of Pt–Pd nanocages and Pt nanorings by conformally coating Pd nanoplates with Pt‐based shells using polyol‐ and water‐based protocols, respectively, followed by selective removal of the Pd cores. For the polyol‐based system, Pd nanoplates were conformally coated with Pt–Pd alloy shells due to the use of a high reaction temperature of 200 °C and a slow injection rate for the Pt precursor. In comparison, Pt shells were formed on Pd nanoplates with a larger thickness on the side face than on the top/bottom face in the water‐based system due to the use of a low reaction temperature of 80 °C and the presence of twin boundaries on the side face. As such, the Pd@Pt nanoplates prepared using the polyol‐ and water‐based protocols evolved into Pt–Pd nanocages and Pt nanorings, respectively, when the Pd templates in the cores were selectively removed by wet etching. The wall thickness of the nanocages and the ridge thickness of the nanorings could be reduced down to 1.1 nm and 1.8 nm, respectively, without breaking the hollow structures. Abstract : Hollowed out : Pt‐based nanocages and nanorings could be controllably fabricated by templating with the same batch of Pd nanoplates using polyol‐ and water‐based protocols, respectively.